Corynebacterium accolens inhibits Staphylococcus aureus induced mucosal barrier disruption - Huang, Shuman; Hon, Karen; Bennett, Catherine; Hu, Hua; Menberu, Martha; Wormald, Peter-John; Zhao, Yulin; Vreugde, Sarah; Liu, Sha (Frontiers in Microbiology, 2022)
Background Corynebacterium accolens (C. accolens) is a common nasal colonizer, while Staphylococcus aureus (S. aureus) is usually considered a pathogenic organism in patients with chronic rhinosinusitis (CRS) . This study aims to evaluate the interaction between two bacteria in vitro. Method Clinical isolates of C. accolens and S. aureus from sinonasal swabs, and primary human nasal epithelial cells (HNECs) cultured from cellular brushings of both healthy and CRS patients were used for this study. The cell-free culture supernatants of all isolates grown alone and in co-cultures were tested for their effects on transepithelial electrical resistance (TER), FITC-Dextran permeability, lactate dehydrogenase (LDH), and IL-6 and IL-8 secretion of HNECs. Confocal scanning laser microscopy and immunofluorescence were also used to visualize the apical junctional complexes. The antimicrobial activity and growth of the C. accolens cell-free culture supernatants on planktonic and biofilm S. aureus growth was also assessed. Results The cell-free culture supernatants of 3 C. accolens strains (at 60% for S. aureus reference strain and 30% concentration for S. aureus clinical strains) inhibited the growth of both the planktonic S. aureus reference and clinical strains significantly. The C. accolens cell-free culture supernatants caused no change in the TER or FITC-Dextran permeability of the HNEC-ALI cultures, while the cell-free culture supernatants of S. aureus strains had a detrimental effect. Cell-free culture supernatants of C. accolens co-cultured with both the clinical and reference strains of S. aureus delayed the S. aureus-dependent mucosal barrier damage in a dose-dependent manner. Conclusion Corynebacterium accolens cell-free culture supernatants appear to inhibit the growth of the S. aureus planktonic bacteria, and may reduce S. aureus-induced damage to the mucosal barrier.